Study of Online Parameter Identification Technology Based on Mathematical Model of Three-phase Asynchronous Induction Motor - Xuedi WANG; Bijun DAI; Yang YANG (机车电传动)
The key of vector control of three-phase asynchronous induction motor is magnetic field orientation and one of the important factors affecting field orientation is the rotor resistance of motor parameters. In order to solve the problem that the dynamic performance of vector control depends on rotor resistance, the on-line identification technology of rotor resistance of three-phase asynchronous induction motor was studied. The mathematical model of induction motor was established. According to the mathematical expression of the motor model, an on-line identification method of rotor resistance was proposed. According to the equivalent circuit diagram of the motor model, the mathematical expression for solving the rotor resistance iteratively was derived.In the process of iteration, the parallel relationship between the voltage and current of the rotor resistance in the space vector diagram of the motor variable was used as the sign to judge the end of calculation. The rotor resistance could be calculated accurately. The experimental results showed that this method could effectively identify the rotor resistance on-line. It is simple to calculate and has high identification accuracy, which meets the needs of engineering applications.